The Syncretic Architecture of the Menara Kudus Mosque as an Expression of Sufistic Tawḥīd - Muhaya, Abdul; Faiq, Muhammad; Arafat, Ahmad Tajuddin; Taufiq, Thiyas Tono (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2024)
Puritan Muslims disapprove of the syncretic architecture of the Menara Kudus Mosque; however, the early Muslim saints spreading Islam in Java adopted this Hindu-Buddhist architectural style as a sign of cultural acceptance and continuity. This study aims to explore the symbolic meanings of the syncretic architecture of the Menara Kudus Mosque built by Sunan Kudus. This qualitative study employs the symbolic interaction theory of Joel M. Charon and George Ritzer, supplemented by the comparative method to unveil the similarities and differences in functions and structures between the Menara Kudus Mosque and Hindu-Buddhist temples and their inherent symbolism can be understood. The study found that Sunan Kudus chose this unique architectural style to promote inclusive and tolerant behavior through a theological-imaginative dialogue process to create social harmony. Such an attitude reflects Sufistic tawḥīd teachings combined with a deep understanding and respect for the local cultures.